Penerapan Diskusi Kelompok Terfokus Berbasis TPACK untuk Meningkatkan Kecakapan Berpikir Kreatif Peserta Didik - Agung Sultoni; Harianingsih; Ellianawati; Decky Avrilianda (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
The purpose of this research is to determine how the implementation of TPACK-based FGDs can improve students' creative thinking skills. This research uses a qualitative approach with a case study method. The subjects of this research were 32 students from class IX D and 1 Pancasila education teacher. The saturated sampling technique used in this study, meaning all students (32 students) were sampled. Data collection techniques were carried out through interviews, observation, and documentation. The data analysis technique used an interactive model, namely data reduction, data presentation, drawing conclusions, and verification. The results of the study indicate that TPACK-based focus group discussion learning can improve students' creative thinking skills in Pancasila education by integrating technology (online collaborative platforms), pedagogy (focus group discussions), and Pancasila content (tolerance on social media) to create meaningful learning experiences. Through this model, students can be encouraged to actively analyze problems, solve problems creatively, and interact with Pancasila materials using digital tools, which ultimately improves students' creativity skills. The implication is that teachers need to master the integration of technology in learning, schools must provide support for facilities and training, and the curriculum needs to be designed to be more contextual and innovative. Keywords: Focus Group Discussion Method, TPACK, Civics Education, Creative Thinking Skill